Consumer Behavior and Trust Deficits in Digital Adhesion Contracts among Philippine E-Wallet Users - Pacubas, Christina Y.; Armas, Kenneth L. (International Review of Management and Marketing, 2026)
The digital financial landscape in the Philippines has rapidly transitioned into a hub for electronic wallet innovation, yet this adoption is governed by digital adhesion contracts that create a profound "consent paradox." This study investigates the interplay between consumer behavior and trust deficits within these "take-it-or-leave-it" agreements. Utilizing a quantitative descriptive-correlational design, data were gathered from 385 adult e-wallet users in major Philippine urban centers and analyzed through multiple linear regression and partial least squares structural equation modeling. The results reveal a stark awareness-behavior gap, where "terms of service fatigue" and the "necessity of service" act as the primary predictors of blind contract acceptance. Furthermore, findings highlight a significant trust deficit exacerbated by escalating cybercrime and "conclusive presumption" clauses that shift the burden of security entirely onto the consumer. Behavioral analysis also confirms a phenomenon termed "spendception," where the frictionless nature of digital payments leads to a 70% impulse purchase rate compared to 25% among cash-focused users. The study concludes that the current legal framework fails to address the "digital bailment" relationship, leaving users vulnerable to proprietary risk allocation. These implications suggest that regulators must reform consumer protection laws to address unconscionable clauses, while providers should adopt human-centered design strategies, such as progressive disclosure, to foster genuine informed consent and maintain long-term ecosystem trust.